2010
DOI: 10.1590/s1516-35982010000600004
|View full text |Cite
|
Sign up to set email alerts
|

Hidrólise da cana-de-açúcar com cal virgem ou cal hidratada

Abstract: RESUMO -Objetivou-se estudar o efeito do tratamento alcalino da cana-de-açúcar com cal virgem ou cal hidratada sobre a composição bromatológica e a digestibilidade in vitro da matéria seca, da fibra em detergente neutro e da fibra em detergente ácido. Utilizou-se um delineamento inteiramente casualizado em esquema fatorial 3 × 3, composto de três formas de processamento da cana (in natura; cana hidrolisada com 0,5% de cal virgem; e cana hidrolisada com 0,5% de cal hidratada) e três tempos de armazenamento (12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1
6

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
4
8
1
6
Order By: Relevance
“…The lack of effect of CaO on lignin content of forage was verified in other studies such as those found by Carvalho et al (2009), who when treating the crushed sugar cane with CaO (0, 1.25, 2.5 and 3.75% DM basis) for 12 and 36h did not observe any influence of the levels of CaO and periods of no treatment in lignin content. Mota et al (2010) obtained a similar result with the hydrolysis of sugar cane, lime or hydrated lime, where the lignin content showed no changes.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The lack of effect of CaO on lignin content of forage was verified in other studies such as those found by Carvalho et al (2009), who when treating the crushed sugar cane with CaO (0, 1.25, 2.5 and 3.75% DM basis) for 12 and 36h did not observe any influence of the levels of CaO and periods of no treatment in lignin content. Mota et al (2010) obtained a similar result with the hydrolysis of sugar cane, lime or hydrated lime, where the lignin content showed no changes.…”
Section: Resultssupporting
confidence: 63%
“…The lack of any significant effect on the EE content in sugar cane caused by the levels of CaO can be explained by the lack of this component in the additive, which did not have any contribution to the EE content in the material changed. Mota et al (2010), who used 0.5% for each treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse material hidrolisado foi desidratado até atingir em torno de 30% da matéria seca e armazenado em tambor plástico de 200 litros com tampa removível para uso durante duas semanas. A ação do óxido de cálcio está relacionada à solubilização parcial da hemicelulose, promovendo o fenômeno conhecido como intumescimento alcalino da celulose -processo de expansão das moléculas de celulose, causando ruptura das ligações intermoleculares das pontes de hidrogênio, que conferem cristalinidade à estrutura e aumento na digestão da celulose e hemicelulose (Jackson, 1997;Mota et al, 2010).…”
Section: Methodsunclassified
“…forage (MOTA et al, 2010). Soybean meal is the protein concentrate commonly used in dairy farming for being a feedstuff of proven high nutritional quality.…”
Section: Introductionmentioning
confidence: 99%